2004
DOI: 10.1016/s1350-4177(03)00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Saccharomyces cerevisiae by ultrasonic irradiation

Abstract: We have investigated the inactivation of Saccharomyces cerevisiae (yeast cells) by ultrasonic irradiation. The amplitude on the vibration face contacting the sample solution was used as an indication of the ultrasonic power intensity. The effects of the amplitude on the vibration face and the initial cell numbers on the sonolytic inactivation of yeast cells have been investigated using a horn-type sonicator (27.5 kHz). The inactivation of the yeast cells by ultrasonic irradiation shows pseudo first-order behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 7 publications
0
34
0
5
Order By: Relevance
“…Microbicidal/static effects associated with cavitation are thought to result predominantly from external mechanical shear forces in a liquid continuum that damage microbial cells in suspension, as well as from cavitation occurring within the cell itself (Ciccolini et al, 1997;Hughes & Nyborg, 1962). The chemical effects of cavitation-induced free radicals in aqueous solution are thought not to be microbicidal (Furuta et al, 2004;Tsukamoto et al, 2004b).…”
Section: Exposure Of S Cerevisiae To Ultrasonicationmentioning
confidence: 99%
“…Microbicidal/static effects associated with cavitation are thought to result predominantly from external mechanical shear forces in a liquid continuum that damage microbial cells in suspension, as well as from cavitation occurring within the cell itself (Ciccolini et al, 1997;Hughes & Nyborg, 1962). The chemical effects of cavitation-induced free radicals in aqueous solution are thought not to be microbicidal (Furuta et al, 2004;Tsukamoto et al, 2004b).…”
Section: Exposure Of S Cerevisiae To Ultrasonicationmentioning
confidence: 99%
“…Several studies have also reported the use of ultrasound for microbial inactivation in other media. Some of the tested microorganisms are Saccharomyces cerevisiae (Guerrero, Tognon, & Alzamora, 2005;Tsukamoto, Constantinoiu, Furuta, Nishimura & Maeda, 2004a;Tsukamoto et al, 2004b;Guerrero, López-Malo, & Alzamora, 2001); Escherichia coli (Ugarte-Romero, Feng, Martin, Cadwallader, & Robinson, 2006;Ananta, Voigt, Zenker, Heinz, & Knorr, 2005;Furuta et al, 2004); L. monocytogenes (Mañas, Pagán, & Raso, 2000;Pagán, Mañas, Alvarez, & Condón, 1999); Salmonella (Cabeza, Ordóñez, Cambero, De la Hoz, & García, 2004); Lactobacillus rhamnosus (Ananta et al, 2005); Yersinia enterocolitica (Raso, Pagán, Condón, & Sala, 1998), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of microbial inactivation are first order or pseudo first order Tsukamoto et al 2004;Zhang et al 2006) with (Guerrero et al 2001;Furuta et al 2004;Tsukamoto et al 2004) and frequency (Borthwick et al 2005). Tsukamoto et al (2004) showed that the rate of inactivation of Saccharomyces cerevisiae yeast cells by ultrasonic irradiation was a function of the amplitude of the ultrasonic wave and the initial cell numbers and was highest at higher amplitudes and lower initial cell numbers.…”
Section: Effects On Microorganismsmentioning
confidence: 99%
“…Tsukamoto et al (2004) showed that the rate of inactivation of Saccharomyces cerevisiae yeast cells by ultrasonic irradiation was a function of the amplitude of the ultrasonic wave and the initial cell numbers and was highest at higher amplitudes and lower initial cell numbers. Subsequently, Borthwick et al (2005) reported that yeast cell disruption was greater in a novel compact 267 kHz sonicator than in a lower frequency 20 kHz probe sonicator at the same exposure time.…”
Section: Effects On Microorganismsmentioning
confidence: 99%